Widely metastatic IDH1-mutant glioblastoma with oligodendroglial features and atypical molecular findings: a case report and review of current challenges in molecular diagnostics - Carlos G. Romo; Doreen N. Palsgrove; Ananyaa Sivakumar; Christen R. Elledge; Lawrence R. Kleinberg; Kaisorn L. Chaichana; Christopher D. Gocke; Fausto J. Rodriguez; Matthias Holdhoff (BMC, 2019)
Abstract Background Gliomas with 1p/19q-codeletion as well as mutation of isocitrate dehydrogenase (IDH) 1 are typically characterized as oligodendrogliomas with comparatively good response to treatment with radiation and chemotherapy. Case presentation We present the case of a 28-year-old man with an IDH1 and TP53 mutant high grade glioma with abnormalities in chromosomes 1 and 19 suggestive of anaplastic oligodendroglioma that rapidly progressed to widespread metastatic disease. Biopsy of a liver lesion confirmed metastasis of the patient's known brain primary and chemotherapy with temozolomide was initiated. The patient's rapidly growing tumor burden with fulminant liver failure and tumor lysis led to multisystem failure of which the patient died. Further molecular testing illustrated features more consistent with glioblastoma: multiple large chromosomal aberrations including loss of whole chromosome 1 and 2q; gain/amplification of MYCN, MET, and CDK4; loss of CDKN2A/B; and an ATRX mutation. Conclusion This case illustrates the importance of higher level molecular diagnostic testing for patients with particularly aggressive disease progression that is not concordant with standard prognoses. Additional data on cases with atypical alterations of 1p and 19q are needed to better understand the distinct biology of these cancers so that appropriate therapies can be developed.